Pain as one of the risk factors for progression of knee osteoarthrosis - Natalia Gavriilovna Kashevarova; E M Zaitseva; A V Smirnov; L I Alekseeva (Научно-практическая ревматология)
Objective: to study the impact of pain intensity on the progression of knee osteoarthrosis (OA). Subjects and methods. One hundred and ten patients with knee OA were examined at a 5-year interval. All the patients underwent a questionnaire survey and knee joint pain assessment using a visual analog scale (VAS) and standard radiography. Results. After 5-year follow-up, radiographic OA progression was seen in 40 patients (Group 2); its stage remained the same in 70 patients (Group 1). In both groups, the patients were matched for age (59.2+9.5 and 59.0+8.1 years) and disease duration (11.1+10.6 and 13.7+9.9 years). During the first examination, pain on walking was more severe in Group 1 than in Group 2: 57.8+16.6 and 48.7+13.3 mm by VAS (р=0.002), as well as severe joint pain was predominant in these patients: 22.5 and 11.4%, respectively. Over the 5-year period, there was an increase in pain intensity. At the end of the follow-up, the patients with progressive OA rated their knee joint pain as severe in 35% of cases whereas in this index the non-progression group was only 12.9 (p = 0.012). Conclusion. In the OA progression group, pain intensity was initially statistically higher than that in the non-progression group. During 5-year follow-up, Group 1 showed an increase in knee joint pain intensity on walking, which can be considered as one of the predictors of gonarthrosis progression.